Predictors of all-cause mortality for patients undergoing transvenous lead extraction. (19th May 2022) - Azari, A; Kristjansdottir, I; Gatti, P; Gadler, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Risk assessment of TLE patients may be challenging due to incomplete knowledge about possible risk factors for post-TLE outcomes. The aim of this study was to identify predictors of 30-day and 1-year mortality in a large retrospective series of patients undergoing TLE at a high-volume centre. Methods: Medical journals of 893 consecutive patients undergoing TLE between January 1, 2010 and December 31, 2018 were analysed. Univariate logistic regression analysis was performed to identify risk factors. Results: A total of 893 patients were identified. Local infection was the dominant TLE indication (40.5%), and pacemaker was the most common CIED (49.4%). Mean age was 65 + 16 years and 73.0% were males. The median follow up was 3.9 years (IQR, 2.0-6.4 years). Staphylococcus aureus was the most common microorganism found in blood cultures of the systemic infection group (39.9%). A total of 179 (69.4%) systemic infection patients had vegetations on echocardiography, where majority engaged the lead(s). The 30-day and 1 year mortality rates were 2.5% (86.4% had systemic infection) and 9.7% (64.4% had systemic infection), respectively. Per-procedural mortality occurred in 1 patient with systemic infection. Significant predictors of 30-day mortality were low haemoglobin, systemic infection as TLE-indication, clinical frailty scales (CFS) 5-7 and stage 5 chronic kidney disease (CKD). In case of 1-year mortality, age, CRT-P/D (vs ICD), reduced ejection fraction, anaemia, BMI <25 kg/m2, CFS 4-7 and CKD stages 3-5 were identified as significant predictors. In the systemic infection subgroup, elevated white blood cell (WBC) count was associated with 30-day and 1 year mortality. Additionally CRP interval 200-300, low WBC count and WBC interval 8.8-15 correlated signigicantly with 1-year mortality within the systemic infection cohort. In the local infection subgroup, a significant correlation between CRP interval 100-150 and 1-year mortality was found. Conclusions: Systemic infection as TLE-indication carries a high 30-days post-TLE all-cause mortality rate and is significantly correlated with short and long-term mortality, where elevated inflammatory parameters carried additional mortality risk in this subgroup. Anaemia, chronic kidney disease, CRT compared to ICD, reduced EF and patient-related features as high clinical frailty scale levels and BMI <25 kg/m2 predicted worse prognosis in the entire TLE-cohort.